A method for preparing polyurethane conductive diaphragm loaded with carbon nanotubes
By loading carbon nanotubes on polyurethane nano -fiber film, a polyurethane conductivity diaphragm with high electrical and stretch stability is prepared to solve the problem of insufficient conductivity and stretch stability in existing technologies. It is suitable for flexible stress sensors. Essence
Patent Information
- Application Number
- CN202210804194.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-07-07
Smart Images

Figure CN115132424B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery materials, and in particular relates to a method for preparing a polyurethane conductive diaphragm loaded with carbon nanotubes. Background Art
[0002] As electronic devices develop towards greater integration, portability, and intelligence, nanofiber films with high conductivity and good stretchability are key materials for flexible stress sensors, and their application in flexible wearable electronics has attracted widespread attention. Polyurethane (PU), with its thermoplasticity, high elasticity, and wear resistance, can be used as a flexible substrate material in sensors. Carbon nanotubes (CNTs), with their excellent electrical and mechanical properties, can be used to enhance the conductivity of flexible substrate materials.
[0003] Chinese Patent Application Publication No. CN111710472A discloses a method for preparing a thermoplastic polyurethane film loaded with multi-walled carbon nanotubes. The method involves pre-treating the carbon nanotubes to obtain carboxylated carbon nanotubes. The carboxylated carbon nanotubes and polyurethane are then ultrasonically dispersed in a solvent to obtain a uniform CNTs / TPU composite solution. This film is then electrospun to form a film. This method significantly improves the specific mechanical properties of the thermoplastic polyurethane film composite, but its electrical conductivity and tensile stability require improvement, making it unsuitable for flexible stress sensors. Therefore, there is an urgent need for a method for preparing a conductive film with high electrical conductivity and tensile stability suitable for flexible stress sensors. Summary of the Invention
[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and provide a method for preparing a polyurethane conductive diaphragm with carbon nanotubes that has high conductivity and tensile stability and is suitable for flexible stress sensors.
[0005] To achieve the above objectives, the present invention provides the following technical solutions:
[0006] A method for preparing a polyurethane conductive diaphragm loaded with carbon nanotubes, the preparation method is carried out in the following steps:
[0007] S1, first adding polyurethane PU to N,N-dimethylformamide and mixing uniformly to obtain solution A, then centrifugally spinning solution A to obtain polyurethane nanofibers, and finally collecting the polyurethane nanofibers and pressing them into a polyurethane nanofiber film;
[0008] S2. First, immerse the polyurethane nanofiber film in a carbon nanotube CNTs dispersion, then take it out and wash and dry it in sequence. Repeat step S2 n times to obtain a polyurethane conductive membrane loaded with carbon nanotubes.
[0009] In step S2, the mass percentage concentration of the carbon nanotube CNTs dispersion is 3-15%.
[0010] In step S2, the mass percentage concentration of the carbon nanotube CNTs dispersion is 6-12%.
[0011] In step S2, n is 3 times, the first immersion time is 8-10 hours, after the second immersion, ultrasonic dispersion is performed for 1-1.5 hours, and then the mixture is taken out and washed and dried in sequence, and the third immersion time is 12-14 hours.
[0012] In step S1, the mass percentage concentration of the solution A is 17-19%.
[0013] In step S1, the rotation speed of the centrifugal spinning is 4400-4600 r / min, and the collection distance is 28-32 cm.
[0014] In step S1, the mixing is specifically stirring at 78-82° C. for 7.5-8.5 hours.
[0015] In step S1, the polyurethane nanofibers are collected by overlapping the polyurethane nanofibers 6-7 times along their orientation, and the polyurethane nanofibers are pressed by pressing them with a weight of 2-2.5 kg and then drying them at 58-62° C. for 2-2.5 hours.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] The present invention discloses a method for preparing a polyurethane conductive membrane loaded with carbon nanotubes. Polyurethane (PU) is first added to N,N-dimethylformamide and mixed uniformly to obtain a solution A. Solution A is then centrifugally spun to obtain polyurethane nanofibers. The polyurethane nanofibers are collected and pressed into a polyurethane nanofiber film. The polyurethane nanofiber film is then immersed in a carbon nanotube (CNT) dispersion solution, removed, cleaned, and dried repeatedly in a cycle n times to obtain a polyurethane conductive membrane loaded with carbon nanotubes. This method loads carbon nanotubes on the surface of the polyurethane nanofiber film, resulting in a controllable thickness and a polyurethane conductive membrane having the flexibility of a polyurethane nanofiber film, as well as high tensile stability and electrical conductivity. Therefore, the present invention combines the flexibility of a polyurethane nanofiber film with high tensile and electrical conductivity, and is suitable for use in flexible stress sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Graph showing the resistance change rate versus stretching rate for test examples 1-5 of the present invention.
[0019] Figure 2 It is the resistance change rate of Test Example 1 in the present invention during different cyclic stretching processes.
[0020] Figure 3 It is the resistance change rate of Test Example 2 in the present invention during different cyclic stretching processes.
[0021] Figure 4 It is the resistance change rate of Test Example 3 in the present invention during different cyclic stretching processes.
[0022] Figure 5 It is the resistance change rate of Test Example 4 in the present invention during different cyclic stretching processes.
[0023] Figure 6 It is the resistance change rate of Test Example 5 in the present invention during different cyclic stretching processes.
[0024] Figure 7 This is the resistance change at the human finger joint in Test Example 3 of the present invention.
[0025] Figure 8 This is the resistance change at the human wrist joint in Test Example 3 of the present invention.
[0026] Figure 9 This is the resistance change at the Adam's apple of the human body in Test Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The present invention will be further described below with reference to the accompanying drawings and specific implementation methods.
[0028] A method for preparing a polyurethane conductive diaphragm loaded with carbon nanotubes, the preparation method is carried out in the following steps:
[0029] S1, first adding polyurethane PU to N,N-dimethylformamide and mixing uniformly to obtain solution A, then centrifugally spinning solution A to obtain polyurethane nanofibers, and finally collecting the polyurethane nanofibers and pressing them into a polyurethane nanofiber film;
[0030] S2. First, immerse the polyurethane nanofiber film in a carbon nanotube CNTs dispersion, then take it out and wash and dry it in sequence. Repeat step S2 n times to obtain a polyurethane conductive membrane loaded with carbon nanotubes.
[0031] In step S2, the mass percentage concentration of the carbon nanotube CNTs dispersion is 3-15%.
[0032] In step S2, the mass percentage concentration of the carbon nanotube CNTs dispersion is 6-12%.
[0033] In step S2, n is 3 times, the first immersion time is 8-10 hours, the second immersion is followed by ultrasonic dispersion for 1-1.5 hours, and then the mixture is taken out for cleaning and drying in sequence, and the third immersion time is 12-14 hours.
[0034] In step S1, the mass percentage concentration of the solution A is 17-19%.
[0035] In step S1, the rotation speed of the centrifugal spinning is 4400-4600 r / min, and the collection distance is 28-32 cm.
[0036] In step S1, the mixing is specifically stirring at 78-82° C. for 7.5-8.5 hours.
[0037] In step S1, the polyurethane nanofibers are collected by overlapping the polyurethane nanofibers 6-7 times along their orientation, and the polyurethane nanofibers are pressed by pressing them with a 2-2.5 kg weight and then drying them at 58-62° C. for 2-2.5 hours.
[0038] The principle of the present invention is described as follows:
[0039] The polyurethane conductive diaphragm loaded with carbon nanotubes prepared by the method of the present invention has high conductivity and stretchability, can adapt to deformation of any shape, and can be directly attached to the surface of human skin to detect movement changes of human body joints.
[0040] Example 1:
[0041] A method for preparing a polyurethane conductive diaphragm loaded with carbon nanotubes is specifically carried out according to the following steps:
[0042] S1. First, polyurethane PU was added to N,N-dimethylformamide in a desired proportion, and stirred at 80° C. for 8 h in a magnetic stirrer to obtain solution A, wherein the mass percentage concentration of solution A was 19%;
[0043] S2. Injecting the solution A obtained in step S1 into a centrifugal spinning machine, adjusting the speed of the centrifugal spinning machine to 4600 r / min and the collection distance to 32 cm to obtain polyurethane nanofibers;
[0044] S3, first overlapping the polyurethane nanofibers along their fiber orientation six times, then pressing them with a 2 kg weight and drying them at 62°C for 2.5 h to obtain a polyurethane nanofiber film with a thickness of 45 μm;
[0045] S4. First, immerse the polyurethane nanofiber film obtained in step S3 in a carbon nanotube CNTs dispersion, then wash it with plasma water and dry it. Repeat step S4 three times to obtain a polyurethane conductive membrane loaded with carbon nanotubes, wherein the mass percentage concentration of the carbon nanotube CNTs dispersion is 6%. The first immersion time is 10 hours. After the second immersion, ultrasonic dispersion is performed for 1 hour and then the film is taken out for washing and drying in sequence. The third immersion time is 12 hours.
[0046] Example 2:
[0047] The difference from Example 1 is that:
[0048] In step S1, the mass percentage concentration of the solution A is 17%;
[0049] In step S2, the rotation speed of the centrifugal spinning machine is 4400 r / min, and the collection distance is 28 cm;
[0050] In step S3, the polyurethane nanofibers were overlapped 7 times along the fiber orientation, and then pressed with a 2.5 kg weight and dried at 58° C. for 2 h to obtain a polyurethane nanofiber film with a thickness of 46 μm;
[0051] In step S4, the mass percentage concentration of the carbon nanotube CNTs dispersion is 3%, the first immersion time is 8 hours, the second immersion is followed by ultrasonic dispersion for 1.5 hours, then taken out for washing and drying, and the third immersion time is 14 hours.
[0052] Example 3:
[0053] The difference from Example 1 is that:
[0054] In step S1, the mass percentage concentration of the solution A is 18%;
[0055] In step S1, the rotation speed of the centrifugal spinning machine is 4500 r / min, and the collection distance is 30 cm;
[0056] In step S3, drying at 60° C. for 2 h yields a polyurethane nanofiber film with a thickness of 45 μm;
[0057] In step S4, the mass percentage concentration of the carbon nanotubes (CNTs) dispersion is 9%.
[0058] Example 4:
[0059] The difference from Example 3 is that:
[0060] In step S4, the mass percentage concentration of the carbon nanotubes (CNTs) dispersion is 12%.
[0061] Example 5:
[0062] The difference from Example 3 is that:
[0063] In step S4, the mass percentage concentration of the carbon nanotube CNTs dispersion is 15%.
[0064] Performance testing:
[0065] 1. Tensile conductivity test
[0066] The conductive diaphragm prepared in Example 2 was used as Test Example 1, the conductive diaphragm prepared in Example 1 was used as Test Example 2, the conductive diaphragm prepared in Example 3 was used as Test Example 3, the conductive diaphragm prepared in Example 4 was used as Test Example 4, and the conductive diaphragm prepared in Example 5 was used as Test Example 5. After being cut into 1 cm*4 cm strips, the initial resistance values of Test Examples 1-5 at 0% stretching rate were first tested using a textile dynamic resistance tester. The initial resistance values of Test Examples 1-5 were measured to be 3265Ω, 3332Ω, 6994Ω, 4795Ω, 3265Ω and 6605Ω, respectively. Then, the resistance change rates of Test Examples 1-5 within 20% stretching rate were tested at a stretching speed of 30 mm / min. The resistance change rates of Test Examples 1-5 as the stretching rate changed were shown in FIG. Figure 1 The cyclic stretching test was performed 20 times in total, with the maximum stretching rate of each cycle being 20%. The resistance change rates of test examples 1-5 during different cyclic stretching processes are shown in Table 1. Figure 2-6 :
[0067] Depend on Figure 1 It can be seen that the resistance change rate of the polyurethane conductive diaphragm loaded with carbon nanotubes increases with the increase of the stretching rate. Among them, the change of test example 3 (9% CNTs) is the most obvious, followed by test example 4 (12% CNTs). Figure 1 The sensitivity gauge factor (GF) of the polyurethane conductive diaphragm at different stretching rates can be obtained by fitting calculation. When the stretching rate is 20%, the GF value of test example 3 is 13.1, while that of test example 1 is only 4.9, that of test example 2 is only 6.0, that of test example 4 is only 6.9, and that of test example 5 is only 6.2.
[0068] Depend on Figure 2 、 Figure 3 It can be seen that the resistance change rate peak values of test case 1 and test case 2 fluctuate within 0.78-0.95, the average resistance change rate is 0.85, and the resistance change rate fluctuation value is about 20%. Figure 4 It can be seen that the resistance change rate peak value of test case 3 fluctuates within 1.9-2.15, the average resistance change rate is 2.0, and the resistance change rate fluctuation value is about 12.5%. Figure 5 It can be seen that the resistance change rate peak value of test example 4 fluctuates within 1.6-2.05, the average resistance change rate is 1.8, and the resistance change rate fluctuation value is about 25%. Figure 6It can be seen that the resistance change rate peak value of Test Example 5 fluctuates within the range of 1.0-1.18, the average resistance change rate is 1.12, and the resistance change rate fluctuation value is about 16.1%. This is because the CNTs loading on the conductive films of Test Examples 1 and 2 is very small, and the resistance change during the stretching process is not obvious. In Test Examples 4 and 5, due to the high concentration of the CNTs dispersion impregnated, the CNTs on the conductive films are stacked and entangled, resulting in little damage to the conductive network during the stretching process, and the resistance change during the stretching process is also not obvious.
[0069] It can be seen that the conductive diaphragm prepared by this method has a high resistance change rate, and has good sensitivity for testing the human body. In addition, the resistance change rate of the conductive diaphragm has a small fluctuation value, and has high accuracy for testing the human body and strong working stability. For verification, the following human body parts tests were conducted using Test Example 3:
[0070] First, cut the test example 3 into 1cm*3cm strips. Then, apply the long strips of conductive film to the fingers, wrists, and Adam's apple of the human body. Then, connect the two ends of the conductive film to the digital oscilloscope through copper glue. The digital oscilloscope is used to record the changes in resistance value during the test to reflect the movement of the human body parts. Among them, when the test example 3 is applied to the human finger joints, the finger joints are bent back and forth 8 times (0-90° bending) within 30 seconds. The monitoring results of the resistance value change are shown in Figure 7 In test example 3, when the wrist joint is attached to the human body, the wrist joint is bent back and forth 6 times (0-90° bending) within 30 seconds. The monitoring results of the resistance value change are shown in Figure 8 In test example 3, when the device is attached to the Adam's apple of the human body, the Adam's apple is made to increase the sound volume in sequence, causing the Adam's apple to vibrate with different amplitudes. The monitoring results of the resistance value change are shown in Figure 9 :
[0071] Depend on Figure 7 It can be seen that the initial resistance of the conductive film is about 12000Ω. Even after 8 cycles of stretching, its resistance remains stable at about 12000Ω. In the figure, the LM segment is the resistance change during the bending process of the finger joint. During the bending process, as the bending angle of the finger joint gradually increases, the corresponding resistance value also increases. The MN segment is the resistance change during the straightening and recovery process of the finger joint. During the straightening and recovery process, as the bending angle of the finger joint gradually decreases, the corresponding resistance value also gradually decreases. It can be seen that the conductive film shows regular changes at the finger joint detection point, and the work is relatively stable, which can be used to monitor the movement of human finger joints.
[0072] Depend on Figure 8It can be seen that the initial resistance of the conductive film is about 25000Ω. Even after 6 cycles of stretching, its resistance is still stable at about 25000Ω. After each cycle, the resistance value fluctuates slightly when it is bent again. This is because the conductive film is attached to the wrist and the wrist is subjected to uneven force when it is bent. In the figure, the OP segment is the resistance change during the extension and bending of the wrist joint. During the bending of the wrist joint, as the bending angle of the wrist joint gradually increases, the corresponding resistance value also becomes larger and larger. The PQ segment is the resistance change during the recovery of the wrist joint. During the recovery of the wrist joint, as the bending angle of the wrist joint gradually decreases, the corresponding resistance value also gradually decreases. It can be seen that the conductive film shows regular changes at the wrist joint detection point, and the work is relatively stable, which can be used to monitor the movement of the human wrist joint.
[0073] Depend on Figure 9 It can be seen that as the sound volume increases, the resistance peak also increases. When the sound volume changes, there are some small peaks, but they do not affect the test results. It can be seen that the conductive film is used to monitor the movement of the human vocal organs.
[0074] In summary, the conductive film prepared by the method of the present invention has high conductivity and stretchability, and is suitable for flexible stress sensors.
[0075] 2. Thermal stability test
[0076] The thermal stability of Test Example 3 and a conventional PU film was tested using a thermogravimetric analyzer (TGA, NETZSCH TG 209F1 model). The test results showed that Test Example 3 began to decompose at a temperature of 325°C, while the conventional PU film began to decompose at 275°C. This shows that the thermal stability of the conductive diaphragm prepared by this method is improved.
Claims
1. A method for preparing a polyurethane conductive diaphragm loaded with carbon nanotubes, characterized in that: The preparation method is carried out in the following steps: S1, firstly adding polyurethane PU into N,N-dimethylformamide and mixing evenly to obtain solution A, then centrifugally spinning solution A to obtain polyurethane nanofibers, and finally collecting the polyurethane nanofibers and pressing them into polyurethane nanofiber films; The mass percentage concentration of the solution A is 17-19%; the rotation speed of the centrifugal spinning is 4400-4600 r / min, and the collection distance is 28-32 cm; the mixing is specifically stirred at 78-82° C. for 7.5-8.5 hours; the polyurethane nanofibers are collected specifically by overlapping the polyurethane nanofibers along their orientation for 6-7 times, and the polyurethane nanofibers are pressed specifically by first pressing with a 2-2.5 kg weight and then drying at 58-62° C. for 2-2.5 hours; S2, first immersing the polyurethane nanofiber film into the carbon nanotube CNTs dispersion, then taking it out and washing and drying it in sequence, and repeating step S2 n times to obtain a polyurethane conductive diaphragm loaded with carbon nanotubes; The mass percentage concentration of the carbon nanotube CNTs dispersion is 9%; n is 3 times, the first immersion time is 8-10 hours, the second immersion is first ultrasonically dispersed for 1-1.5 hours and then taken out for washing and drying in sequence, and the third immersion time is 12-14 hours.
Citation Information
Patent Citations
Carbon nanotube transparent conductive film and preparation method thereof
CN111710472A
Electrochromic yarn and preparation method thereof
CN109610057A
Multifunctional flexible sensing fiber membrane and preparation method and application thereof
CN111118889A
Preparation method of fiber-based anisotropic stretchable conductor
CN113782278A